Hopping in a Molecular Wire - Marco, R.; Banzon, R.; Villagonzalo, C. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
Excerpt We utilize the Hubbard model approach in analyzing the effect of the hopping parameter in the transport properties of a two-atom molecular device (Kostyrko & Bulka, 2003). The system consists of a molecule with two identical atoms connecting two metal electrodes. In this model, two important and realistic energy parameters are considered which affects the transport properties. The first is the kinetic energy required to “hop” from one atomic site to the next. We call this parameter the hopping term denoted by t, in arbitrary units of energy. The next is an on-site Coulombic repulsion, U, between two electrons on the same atomic site.